The role of MscL amphipathic N terminus indicates a blueprint for bilayer-mediated gating of mechanosensitive channels - Navid Bavi (Nature Portfolio, 2016)
The activation of bacterial mechanosensitive channels is still not fully understood. Here, Bavi et al. show that the N-terminal helix of MscL dynamically couples membrane tension to channel gating, suggesting a conserved mechanism underlying the mechanosensitivity of ion channels of higher organisms.